Real-world effectiveness of anti-TNF switching in psoriatic arthritis: a systematic review of the literature. Issue 12 (December 2016) - Reddy, Soumya; Crean, Sheila; Martin, Amber; Burns, Meghan; Palmer, Jacqueline
Abstract Anti-tumor necrosis factors (Anti-TNFs) are a class of biologic disease-modifying anti-rheumatic drugs indicated for the treatment of moderate-to-severe psoriatic arthritis (PsA). Refractory patients are commonly managed by switching from one anti-TNF to another. To assess the evidence on the effectiveness of anti-TNF cycling in PsA patients, a systematic review of the literature was conducted. MEDLINE- and Embase-indexed English-language publications were systematically searched from 1995 to 2015 for studies assessing real-world effectiveness outcomes of anti-TNF cycling in PsA patients. Of 1086 citations identified, 18 studies were included; most conducted in Europe. Six of seven studies testing between lines found significant differences in effectiveness between earlier and subsequent lines of anti-TNF therapy. First-line therapy yielded better results compared with second-line therapy, and significant differences were observed between second- and third-line anti-TNF treatments. In the only study with multivariate regression testing for predictors of response, Danish registry patients were less likely to respond (American College of Rheumatology 20 % or 50 % response) to a second anti-TNF course if safety, rather than lack of effect, caused them to switch (odds ratio [OR] 0.04;p  = 0.003 and OR 0.05;p  = 0.03, respectively). Effectiveness of anti-TNFs at second line and later is reported in a small number of real-world studies of PsA patients. Subsequent treatment lines may be associated with less response in some measures. More research is needed to quantify the effectiveness of sequential anti-TNF lines in this progressive population‚ and to compare these effects with responses to drugs with different mechanisms of action.